Analytic study of endoscopic findings in patients with upper gastrointestinal bleeding at Tishreen University Hospital in 2022 - 2023 - راجح عبد القادر; اسماعيل حمَاد; ميلاد أنطانيوس (Latakia University Journal -Medical Sciences Series, 2023)
Background : Upper gastrointestinal bleeding (UGIB) remains a life-threatening medical problem that is common worldwide. It is an emergency medical condition, which may require hospital admission. UGIB also increases the risk of morbidity, and mortality , so it warrants early evaluation. Upper gastrointestinal endoscopy is the main diagnostic and therapeutic procedure for upper gastrointestinal bleeding. Objective : To determine the endoscopic findings in patients presenting with UGIB and its frequency among these patients according to gender and age at Tishreen University Hospital in 2022 - 2023. Materials and Methods : The study was carried out in the Department of Gastrointestinal at Tishreen University Hospital in 2022 - 2023. The record of patients admitted with upper GI bleed through indoor/outdoor was retrieved from the Department of Gastrointestinal. 408 Patients fulfilling inclusion criteria were selected in the study. The relevant data and endoscopic findings were documented on Performa. The data was prospective, descriptive, cross-sectional study. Results : A total of 408 patients had endoscopy for UGIB which consisted of 229 (56.13%) males and 179 (43.87%) females, and the mean age was 55.52 years ± SD 18.29. The commonest cause of UGIB was duodenal ulcer in 112 patients consisting of (27.5%), followed by gastric ulcer in 89 patients (21.9%), gastritis in 48 patients (11.9%) and esophageal and gastric varices were in 25 patients (6.3%). Malignant conditions (cancers) contributed to (6%), which included esophageal cancer in two patients (0.5%), gastric cancer in 21 patients (4.3%), and duodenal cancer in 5 patients (1.2%). Esophagitis was in 24 patients (5.9%). Other less frequent causes of UGIB were Mallory-Weiss tear in 9 patients (2.3%), gastroduodenitis in 8 patients (2%), duodenitis in 8 patients (2%), angiodysplasia of stomach in 6 patients (1.6%), esophageal ulcer in 4 patients (1%), angiodysplasia of duodenum in two patients (0.5%), gastric polyps in one patient (0.3%). Normal endoscopic findings were in 44 patients (10.8%) in patients who had UGIB. Conclusion : Peptic ulcer disease which included duodenal and gastric ulcers was the commonest cause of UGIB in our population followed by gastritis, while gastric polyps were the rarest cause. Key words : Endoscopy, upper gastrointestinal bleeding (UGIB), Peptic ulcer disease.